Pengaruh Motivasi Kerja dan Stres Kerja Terhadap Kinerja Pegawai Negeri Sipil pada Kantor Sekretariat DPRD KabupatenPadang Lawas, Provinsi Sumatera Utara - Desvi Emti; Robiatul Adwiyah Harahap (Yayasan Almanar Pujud, 2024)
This research aims to examine the influence of work motivation and work stress on the performance of civil servants at the DPRD Secretariat Office, Padang Lawas Regency, North Sumatra Province. This type of research is quantitative research using multiple linear regression methods. The total sample in this study was 47 respondents selected using the purposive sampling method. Data collection was carried out by distributing questionnaires to respondents. Research data was analyzed using the SPSS V.26 program. The research results show that partially work motivation has a positive and significant effect on employee performance, work stress partially has a negative and significant effect on employee performance. Simultaneously, Motivation and Stress have a significant influence on the Performance of Civil Servants at the Padang Lawas Regency DPRD Secretariat Office. The magnitude of the influence of Work Motivation and Work Stress on the Performance of Civil Servants at the Padang Lawas Regency DPRD Secretariat Office is 60%, the remaining 40% is influenced by other variables not examined in this research.